A systematic review of monitoring and evaluation indicators for sexual and reproductive health in humanitarian settings - Elena T. Broaddus-Shea; Loulou Kobeissi; Osama Ummer; Lale Say (Conflict and Health, 2019)
Abstract Objective To conduct a comprehensive mapping of published indicators for monitoring and evaluation (M&E) of sexual and reproductive health (SRH) services and outcomes in humanitarian settings. Methods A systematic search of the peer-reviewed and grey literature published between January 2008 and May 2018 was conducted to identify all references describing indicator sets for M&E of SRH services and outcomes in humanitarian settings. The databases MEDLINE, Web of Science, and Global Health, as well as 85 websites of relevant organizations involved in humanitarian response were searched. Characteristics of identified indicator sets and data from individual indicators was extracted. Findings Of 3278 records identified, 20 met the review’s inclusion criteria and 9 existing indicator sets were identified. A total of 179 relevant indicators were included in the mapping, and removal of duplicates yielded 132 unique indicators. Twenty-seven percent fell within the maternal health domain, followed by the HIV/AIDS domain (26%) and the gender-based violence domain (23%). The distribution of indicators by type (process/output, outcome, impact) was balanced overall but varied substantially across domains. The most commonly used data collection platforms were facility-based systems or population-based surveys. Domains covered and indicator definitions were inconsistent across indicator sets. Conclusion Results demonstrate the need to standardize data collection efforts for M&E of SRH services and outcomes in humanitarian settings and to critically appraise the extent to which different domains should be covered. A core list of indicators is essential for assessing response status over time as well as across countries.